2015
DOI: 10.1167/iovs.15-17251
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamic AMD-Associated Chronic Oxidative Stress Changes in Human ESC and iPSC-Derived RPE Cells

Abstract: Citation: Garcia TY, Gutierrez M, Reynolds J, Lamba DA. Modeling the dynamic AMD-associated chronic oxidative stress changes in human ESC and iPSC-derived RPE cells. Invest Ophthalmol Vis Sci. 2015;56:7480-7488. DOI:10.1167/iovs.15-17251 PURPOSE. Here we use human embryonic stem cells (hESCs) and human-induced pluripotent stem cell (hiPSC)-derived retinal pigment epithelium (RPE) cells to model chronic oxidative stress in vitro. This model allows us to understand the evolution of chronic stress response in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
1
29
1
3
Order By: Relevance
“…Importantly, the miRNA with the highest number of studies supporting its involvement in AMD is miR-146a. Two studies performed in patients, and three studies performed in human RPE cells or in mouse retinae revealed a miR-146a upregulation, although one study indicated this miRNA species to be downregulated after oxygen-induced retinopathy (OIR) [56, 57, 71, 7375]. Although technically not an AMD model, OIR is a well-established protocol used to study hyperoxia-induced retinal neovascularization and inflammation in mice, two well-known characteristics of AMD [76, 77].…”
Section: Mirna and Amdmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the miRNA with the highest number of studies supporting its involvement in AMD is miR-146a. Two studies performed in patients, and three studies performed in human RPE cells or in mouse retinae revealed a miR-146a upregulation, although one study indicated this miRNA species to be downregulated after oxygen-induced retinopathy (OIR) [56, 57, 71, 7375]. Although technically not an AMD model, OIR is a well-established protocol used to study hyperoxia-induced retinal neovascularization and inflammation in mice, two well-known characteristics of AMD [76, 77].…”
Section: Mirna and Amdmentioning
confidence: 99%
“…b Plasma[103]miR-374ahsa-miR-374a-5p0.1ARPE-19 cellsOxidative stress[82]hsa-miR-374a-5p−12.92Plasma[103]miR-424mmu-miR-424 a +Mouse retinaOIR[90]hsa-miR-424-5p−0.338Plasma[51]hsa-miR-424-5p3.97; 3.28Serum[52]

FC fold change , AMD age-related macular degeneration , miRNA micro RNA , GA AMD graphic atrophy AMD , RPE retinal pigment epithelium, OIR oxygen-induced retinopathy, VH vitreous humor, pro - inf pro-inflammatory, ARPE - 19 adult retinal pigment epithelium cell line

a Mature miRNA strand unknown/not mentioned

b o.p. : miRNA was only expressed in the patient group c Oxidative stress was induced using H 2 O 2 [82] or Paraquat [73] d A “+” indicates miRNA upregulated/higher levels and “−” indicates miRNA downregulated/lower levels

…”
Section: Mirna and Amdmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic oxidative damage in RPE may increase the expression of proteins (see 10 ) and probably causes apoptosis. Stem cellderived RPE was previously used as a model system with chronic, low-level oxidative stress from paraquat (PQ) to study the NRF2-mediated transcriptional responses 11 . PQ is well tolerated by RPE 12 and is a suitable mimic for pathological oxidative stress that occurs in AMD, which is thought to be mostly generated in mitochondria 13 .…”
Section: Introductionmentioning
confidence: 99%